2018
DOI: 10.4103/sajc.sajc_317_16
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of buccal mucosa: An analysis of prognostic factors

Abstract: Introduction:Carcinoma of the buccal mucosa is the most common oral cavity cancer in the Indian subcontinent. The aim of this study was to analyze the outcome and evaluate prognostic factors in surgically treated buccal mucosa squamous cell carcinoma (BMSCC) patients.Materials and Methods:A retrospective study was performed by reviewing the medical records of 409 pathologically proven buccal mucosa cancer patients, who were diagnosed and surgically treated in Tata Memorial Hospital between January 1, 2006, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 41 publications
3
25
0
1
Order By: Relevance
“…A In that study, floor of the mouth and oral tongue represented the most common disease subsites, followed in descending order by gums, retromolar trigone, buccal mucosa, and hard palate [14]. In regions of China, South East Asia, and India, however, carcinoma of the buccal mucosa is one of the most common forms of OSCC [15][16][17] . The difference in the predominant sites of occurrence of cancers may largely be related to various habits prevalent in the respective regions, such as the incidence of OSCC of the buccal mucosa results from the endemic regional practice of chewing betel quid.…”
Section: Discussionmentioning
confidence: 90%
“…A In that study, floor of the mouth and oral tongue represented the most common disease subsites, followed in descending order by gums, retromolar trigone, buccal mucosa, and hard palate [14]. In regions of China, South East Asia, and India, however, carcinoma of the buccal mucosa is one of the most common forms of OSCC [15][16][17] . The difference in the predominant sites of occurrence of cancers may largely be related to various habits prevalent in the respective regions, such as the incidence of OSCC of the buccal mucosa results from the endemic regional practice of chewing betel quid.…”
Section: Discussionmentioning
confidence: 90%
“…Loco-regional metastasis of OSCC to cervical lymph nodes is a very important prognostic factor. The number and size of affected lymph nodes, extra capsular spread and the extent of involvement of the neck, all contribute in determining the prognosis of a patient with oral carcinoma ( 8 ). Staging of patients is done also to define the need for adjuvant therapy in OSCC cases after surgery, because it is proven that in patients with pN+ post-operative radiotherapy reduces chances of recurrence ( 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cervical lymph node metastasis is the main mode of metastasis in various stages of oral cancer, and it is also an important factor affecting the prognosis of oral cancer. The number and size of metastatic lymph nodes, whether or not the capsular invasion, and the extent of involvement of the neck region will directly affect the prognosis of patients 11. Studies have shown that 50% of patients with oral cancer have lymph node metastasis at the first visit 12.…”
Section: Discussionmentioning
confidence: 99%